Traversing barriers to health care among LGBTQ+ Latinx emerging adults: Utilizing patient experiences to model access - Rachel Schmitz; Jennifer Tabler (The Beryl Institute, 2021)
Enduring multiple sources of marginalization, lesbian, gay, bisexual, transgender, and/or queer (LGBTQ+) youth of color living at the United States-Mexico border navigate stigma and health challenges surrounding their LGBTQ+ and ethnic identities. This study sought to delineate barriers to health care experienced by marginalized young adult patients. We qualitatively examined the patient experiences of 41 LGBTQ+ Latinx young adults (ages 18-24) in the Rio Grande Valley between 2016 and 2017. Often tied to their experiences of emerging adulthood, most respondents emphasized how financial barriers, including cost of services and disruptions to insurance status, prevented them from seeking care (barriers to care). However, youth also underscored how prior patient experiences tied to their ethnic and LGBTQ+ identities, including apprehension discussing their sexuality with care providers (barriers within care), shaped their health care seeking strategies. This study utilized patient experiences to delineate potential sources of barriers to care experienced by LGBTQ+ Latinx young adults. Practitioners should seek to actively create inclusive and identity-affirming care environments and be sensitive to how prior negative experiences may be deterring young adult patients from seeking care or revealing personal details during the care encounter. If we are to better model access, we need to consider the patient experiences of diverse populations. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.